BANTUAN HUKUM BAGI MASYARAKAT MISKIN DI PENGADILAN AGAMA CIMAHI TAHUN 2016: Legal Aid for the Poor at the Religious Court of Cimahi in 2016 - Susanto, Yoghi Arief; Kania, Dede; Burhanuddin, Burhanuddin (Asy-Syari'ah, 2018)
AbstractLegal assistance is a constitutional right of every citizen that is non-derogable rights as an effort to fulfil access to justice and equality before the law, especially for the poor and who doesnâ€™t understand law. The implementation of legal assistance in the Cimahi Religious Court are not optimum due to lack of information, the presence of individuals who seeks personal benefits, and a common sense of high cost advocate services. This study is aimed to determine the implementation of legal assistance for the poor in the Cimahi Religious Court along with its supporting factors. This research is a qualitative research with descriptive analytical method and an empirical juridical approach. The utilized data are primary and secondary data. Data collection is done by interview techniques and literature studies. The implementation of legal assistance in the Cimahi Religious Court is still not effective due to legal factors, law enforcement factors, facilities, community factors and cultural factors. The inhibiting factor in legal assistance is a lack of socialization, difficult access for the community, and a culture in apparatus seeking personal gain. Supporting factors in legal assistance include good relations between legal aid agencies, increased awareness of the Village apparatus and KUA, and the existence of Cimahi Religious Court Website.Keywords:legal assistance, equality before the law, poor society.Â AbstrakBantuan hukum merupakan hak konstitusional setiap warga negara yang bersifat non derogable rights sebagai upaya mewujudkan Acces to Justice dan Equality Before The Law terutama untuk masyarakat miskin dan buta hukum. Fenomena yang terjadi di Pengadilan Agama Cimahi masih kurangnya informasi bantuan hukum, adanya oknum yang mencari keuntungan pribadi, dan anggapan mahalnya jasa advokat membuat pelaksanaan bantuan hukum belum maksimal. Penelitian ini bertujuan untuk mengetahui pelaksanaan bantuan hukum bagi masyarakat miskin di Pengadilan Agama Cimahi beserta faktor penghambat dan penunjangnya. Penelitian menggunkn penelitian kualitatif dengan metode Deskriptif Analitis dn pendekatan Yuridis Empiris. Data yang digunakan adalah data Primer dan Sekunder. Pengumpulan data dilakukan dengan teknik wawancara dan studi pustaka. Pelaksanaan bantuan hukum di Pengadilan Agama Cimahi masih belum efektif karena faktor hukum, faktor penegak hukum, faktor sarana, faktor masyarakat dan faktor budaya. Faktor penghambat dalam bantuan hukum adalah kurangnya sosialisasi, akses masyarakat yang masih sulit, dan ada budaya di aparat yang mencari keuntungan pribadi. Faktor penunjang dalam bantuan hukum diantaranya adanya hubungan baik antar lembaga pemberi bantuan hukum, meningkatnya kesadaran perangkat Desa, KUA dan ada Website Pengadilan Agama Cimahi.Kata Kunci :Bantuan Hukum, Equality Before The Law, Masyarakat Miskin